2020
DOI: 10.2147/copd.s236640
|View full text |Cite
|
Sign up to set email alerts
|

<p>Chitinases and Chitinase-Like Proteins in Obstructive Lung Diseases – Current Concepts and Potential Applications</p>

Abstract: Chitinases, enzymes that cleave chitin's chain to low molecular weight chitooligomers, are widely distributed in nature. Mammalian chitinases belong to the 18-glycosyl-hydrolase family and can be divided into two groups: true chitinases with enzymatic activity (AMCase and chitotriosidase) and chitinase-like proteins (CLPs) molecules which can bind to chitin or chitooligosaccharides but lack enzymatic activity (eg, YKL-40). Chitinases are thought to be part of an innate immunity against chitin-containing parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 116 publications
(221 reference statements)
1
26
0
3
Order By: Relevance
“…Immunohistochemistry also shows that the expression levels of CHI3L1 are enhanced in bronchiolar epithelial cells and alveolar macrophages adjacent to brotic lesions of the patients with IPF, suggesting the possible involvement of CHI3L1 in the brotic process of IPF 21 . These ndings together suggest that CHI3L1 plays an important role in the tissue remodelling of respiratory system in COVID-19 following the massive in ammation and alveolar destruction and local tissue remodelling 22,23 . Therefore, higher levels of CHI3L1 might be associated with the pathogenesis of COVID-19 especially in relevance to pulmonary tissue damage and repair.…”
Section: Discussionmentioning
confidence: 85%
“…Immunohistochemistry also shows that the expression levels of CHI3L1 are enhanced in bronchiolar epithelial cells and alveolar macrophages adjacent to brotic lesions of the patients with IPF, suggesting the possible involvement of CHI3L1 in the brotic process of IPF 21 . These ndings together suggest that CHI3L1 plays an important role in the tissue remodelling of respiratory system in COVID-19 following the massive in ammation and alveolar destruction and local tissue remodelling 22,23 . Therefore, higher levels of CHI3L1 might be associated with the pathogenesis of COVID-19 especially in relevance to pulmonary tissue damage and repair.…”
Section: Discussionmentioning
confidence: 85%
“…An important molecular component of both helminths and fungi that signals infection is chitin, which is found in the cuticle and grinder of multiple helminths, and in the cell wall of multiple fungal species (Dickey, 2007;Przysucha et al, 2020). Introduction of chitin into the lungs of mice strongly induces airway epithelial mucous metaplasia and the accumulation of ILC2s and eosinophils (Reese et al, 2007).…”
Section: Sensing Type 2 Pathogen-associated Molecular Patterns Damage-associated Molecular Patterns and Cytokinesmentioning
confidence: 99%
“…Specifically, lumenal mucus traps larvae in the airway lumen, preventing the completion of the parasite life cycle of migration to the gut. Similarly, chitinases and chitinase-like proteins promote resistance to both parasites and fungi, but can also contribute to the pathophysiology of asthma and other airway diseases (Bigot et al, 2020;Przysucha et al, 2020). The roles of multiple other molecules involved in Type 2 epithelial responses have a similar two-sided character, participating both in resistance to helminths and fungi and in the pathogenesis of non-infectious airway diseases (Hammad and Lambrecht, 2021).…”
Section: Anti-infective and Maladaptive Type 2 Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Przysucha et al (2020) reported that, mammals are mainly express chitinases and chitinase-like proteins which are secreted by phagocytes (mainly neutrophils and macrophages). These cells are induced at the sites of in ammation, infection and tissue remodeling.…”
mentioning
confidence: 99%